RANCANG BANGUN MESIN PENGERING BUNGA TELANG TIPE RAK DENGAN TEKNOLOGI INFRARED BURNER - Rika Diana (2023)
Butterfly Pea (Clitoria ternatea) is a flower that contains phytochemicals so that it can be processed into herbal tea for health. The drying process of the butterfly pea was previously carried out by drying through sunlight. This method takes a relatively long time, and the temperature is unstable. Therefore, the purpose of this study is to obtain data on the influence of temperature, moisture content, and time during the drying of butterfly pea. To find out this, a rack-type flower dryer machine was designed that utilises infrared burner technology. The research method starts from design, manufacturing, and trials. The machine is designed with dimensions of 50 x 50 x 50 cm and a capacity 7,05 kg / hour.